IMPROVING STUDENT'S CRITICAL THINKING SKILLS USING THE INQUIRY LESSON MODEL - Noor Fadiawati; Chansyanah Diawati; Galuh Catur Wisnu Prabowo (Universitas Lampung, 2022)
Abstract: This study aims to describe the effectiveness of the inquiry lesson model on the buffer solution material to improve students' critical thinking skills. The research sample was grade XI students of a senior highschool in Bandarlampung which obtained by using purposive sampling technique. In the control class, direct instruction learning was applied and in the experimental class was the inquiry lesson. The research used a quasi-experimental design with The Matching-Only Pretest- Post-test Control Group. The research data were analyzed using the n-gain calculation and parametric statistics with the t-test. The results showed that the post-test average score of critical thinking skills in the experimental class and the control class had a significant difference and the average n-gain in the experimental class was 0.48 (moderate category). Thus, it can be concluded that the Inquiry Lesson model is effective for improving students' critical thinking skills.Keywords: Inquiry lesson, buffer solution, critical thinking skills Abstrak: Penelitian ini bertujuan untuk mendeskripsikan efektivitas model inquiry lesson pada materi larutan penyangga untuk meningkatkan keterampilan berpikir kritis siswa. Populasi dalam penelitian ini adalah seluruh siswa kelas XI IPA sebuah SMA Negeri di Bandarlampung yang diperoleh dengan teknik purposive sampling. Pada kelas kontrol diterapkan pembelajaran langsung dan pada kelas eksperimen diterapkan inquiry lesson. Metode penelitian yang digunakan adalah kuasi eksperimen dengan desain The Matching-Only Pre-test - Post-test Control Group. Data penelitian dianalisis menggunakan perhitungan n-gain dan statistik parametrik dengan uji t. Hasil penelitian menunjukkan bahwa skor rata-rata postes keterampilan berpikir kritis kelas eksperimen dan kelas kontrol memiliki perbedaan yang signifikan serta n-gain rata-rata di kelas eksperimen sebesar 0,48 (berkategori sedang). Dengan demikian, dapat disimpulkan bahwa model Inquiry Lesson efektif untuk meningkatkan keterampilan berpikir kritis siswa. Kata kunci: Inquiry Lesson, larutan penyangga, keterampilan berpikir kritis.